*This preview shows
page 1. Sign up
to
view the full content.*

**Unformatted text preview: **(x + y)(x + y’) = x Adjacency x + x’y = x + y x(x’ + y) = xy Adsorption xy + x’z + yz = xy + x’z (x + y)(x’ + z)(y + z) = (x + y)(x’ + z) Consensus Flip-Flop Tables Characteristic D Q(t+1) 0 0 1 1 J K Q(t+1) 0 0 Q(t) 0 1 0 1 0 1 1 1 Q’(t) S R Q(t+1) 0 0 Q(t) 0 1 0 1 0 1 1 1 X T Q(t+1) 0 Q(t) 1 Q’(t) Excitation Q(t) Q(t+1) D 0 0 0 0 1 1 1 0 0 1 1 1 Q(t) Q(t+1) J K 0 0 0 x 0 1 1 x 1 0 x 1 1 1 x 0 Q(t) Q(t+1) T 0 0 0 0 1 1 1 0 1 1 1 0 Q(t) Q(t+1) S R 0 0 0 x 0 1 1 0 1 0 0 1 1 1 x 0...

View
Full
Document